Factors affecting food delivery riders' intention to participate in the gig economy / Azarisham Shafiei, Rosmah Mohamed and Rozanah Ab Rahman - Shafiei, Azarisham; Mohamed, Rosmah; Ab Rahman, Rozanah (Research Management Institute (RMI), 2022)
Since Covid-19 (C19) became a global pandemic, there has been a rise in the number of people joining food delivery platforms (FDPs). Although this form of gig work is gaining its pace, food delivery riders (FDRs) are falling behind in terms of rules and legislation designed to safeguard their employees. To understand the spread of these unstable forms of employment, it is essential to comprehend the factors that keep FDRs in it. This quantitative study employed PPM to determine the relationship between push, pull, and mooring factors and FDRs' intention to participate in the gig economy; and to test whether these factors prevent or lead to their participative behaviour. The SPSS 26.0 and Smart PLS 3.30 programmes were used to analyse the survey data from 393 respondents. Economic necessities, extra income, flexibility, and control and autonomy, encouraged FDRs' gig economy participation, whereas limited alternatives and enjoyment minimise it. It is also evident that FDRs will have lower participation due to the lack of employment protection that also moderates the relationship between economic necessities and their participation in the gig economy. This research provides widespread implications for both theory and practice.